PENGEMBANGAN E-MODUL BERBANTUAN FLIPHTML5 PADA MATERI KOMPOSISI FUNGSI DAN FUNGSI INVERS UNTUK SISWA KELAS XI SMAN 1 BAYANG - Dara Puspita Sari; Radhya Yusri; Zulfitri Aima (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the teaching materials used at SMAN 1 Bayang in mathematics learning that have not met the needs of students. This study aims to develop a valid and practical E-Module assisted by flipHTML5 on the composition of functions and inverse functions for class XI SMAN 1 Bayang. This type of research is R & D (Research & Development) development research. The development model used is the Plomp development model. In this study, the stages carried out were only at the preliminary research and prototyping phase stages which included validity and practicality tests. Data analysis techniques used were analysis of student characteristics, ATP analysis, analysis of printed books, analysis of interviews with educators and students, analysis of validity results and analysis of practicality results. Based on the results of the data analysis, it was obtained that the developed E-Module obtained a validity result of 86.03% by the validator with a very valid category. The final practicality score for educators was 72.50%, categorized as practical, the final practicality score for students in the one-on-one evaluation was 82.96%, categorized as very practical, and the final practicality score for students in the small group evaluation was 88.89%, categorized as very practical. Based on the research results, it can be concluded that the flipHTML5-assisted E-Module on the composition of functions and inverse functions for class XI of SMAN 1 Bayang is declared valid and practical for use by educators and students in learning activities.